(untitled) (Semiárida, 2020)
Digitaria eriantha Steudel subsp. eriantha is a perennial forage grass originated from Africa, characterized by its productivity and quality. The trial was done close to V. Mercedes of 3 cutting strategies (at flag leaf, first mature panicles and end of the growing stage) and 2 different nitrogen fertilization levels (0 and 127 kgN2/ha) on dry matter (OM) yield, crude protein and in vitro digestibility. The highest yields (P<0.01) were obtained when cutting was done at the end of the growing stage with N2 fertilization, with level a between 9 and 12.5 tnOM/ha depending on the year. The fertillzation favored the Ieaves fraction with no differences (P<0.01) among cutting frequency. Nitrogen utilization efficiency by the cultive varied from 18.9 to 44.6 kgOM.kgN2 depending on the year and the treatment. The apparent recovering of added N2 ranged from 23.6 to 74.3%, being higher in the defoliation treatments. Crude protein content was highest in the leafly fraction (P<0.05) of the fertilized treatment and frequent cutting strategy (13%). At the end of the growing stage C.P was 7 and 5.6 %, fertilized and nonfertilized respectively. The same differences were found for the Iignified fraction, being 9.7 and 7.6% with and without N2. The lowest values were found in the Iignified fraction at the end of the growing stage with 3.7 and 2.6 depending on fertilization. In vitro digestibility was higher in trials with frequent cutting strategies (P<0.05) than in the treatment with one cut at the end of the growing atage, for leafly and Iignified fractions.